1993
DOI: 10.1136/jcp.46.6.540
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Helicobacter pylori DNA in the mouths and stomachs of patients with gastritis using PCR.

Abstract: Aims-To determine the prevalence of Helicobacter pylori colonisation in the mouths of patients with H pyloni gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
3
10

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(136 citation statements)
references
References 15 publications
10
113
3
10
Order By: Relevance
“…A single-step PCR with the primers EHC-U=EHC-L and 40 cycles of ampli®cation consistently detected ®ve H. pylori cells added to saliva or to dental plaque [20]. In contrast, others reported the detection limit to be 10±100 cells of cultured H. pylori [6,8,27,28]. The possibility of false positivity is very unlikely in the present study, because considerable care was taken to prevent contamination, as described by Kwok and Higuchi [23].…”
Section: Discussionmentioning
confidence: 44%
“…A single-step PCR with the primers EHC-U=EHC-L and 40 cycles of ampli®cation consistently detected ®ve H. pylori cells added to saliva or to dental plaque [20]. In contrast, others reported the detection limit to be 10±100 cells of cultured H. pylori [6,8,27,28]. The possibility of false positivity is very unlikely in the present study, because considerable care was taken to prevent contamination, as described by Kwok and Higuchi [23].…”
Section: Discussionmentioning
confidence: 44%
“…Previous comparative studies of the sensitivity of PCR and culture in the detection of H. pylori were mostly based on < 50 samples [19,20, 30- [30] and Clayton et al [20], who found that some patients with normal mucosa were colonised with H. pylori, as well as patients with chronic gastritis who had not been infected with H. pylori. By strictly following the rules for sample transportation times, the present study reduced the risk of making the target micro-organism non-culturable or dead [26].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori survives for a time in gastric juice. All of us reflux slightly from time to time, so it is not surprising that the organism, and more commonly its DNA, has been detected in the mouth, for instance in dental plaque 19,20 . Recent observations in volunteers infected with H. pylori who were made to vomit or have diarrhoea showed that an actively unwell person with these symptoms could spread H. pylori in the immediate vicinity by aerosol, splashing of vomitus, infected vomitus and infected diarrhoea 21 .…”
Section: Epidemiology and Disease Associationsmentioning
confidence: 99%